Arranjos produtivos de turismo com inserção da logística de serviço visando o desenvolvimento local endógeno: estudo do caso de Guaramiranga - Silva, Marília Ribeiro da (2008)
At the current framework in the State of Ceará, characterized by the consequences of a model of economic growth giving emphasis on the urban industrialization concentrated on the Metropolitan Region of Fortaleza (MRF), it is necessary to include other regions of the state and their respective populations. Also, we must decentralize the income generated by the economic activity, which favors only a small m share of the state’s population. Therefore, the use of strategies for endogenous development is essential. In this context, tourism stands out, which in Ceará presents numerous opportunities due to our weather, the privileged geographical location and diversity of landscapes - mountains, seaside and countryside, covering all of the state’s regions in a balanced way. However, in order for tourism to generate benefits for the local population, we must adopt forms of development which are really economically includent. It is in this scenario that the Tourism Local Productive Arrangements – TLPA’s stand out, which can be used as strategies for local development provided that population is really integrated. However, so that such arrangements are sustainable, support is needed to provide good services, as tourism is an activity that requires a high degree of quality of the services offered. In this sense, concepts of logistics applied to tourism services can serve as instruments so that such services are provided adequately and according to customers’ expectations, aiming at the sustainability of local actors, more specifically the owners of accommodation places and restaurants living in the town. For this reason, it was done a survey of excellent proposal of pointers of logistic performance for such tourist establishments. Therefore, we present in this Master’s thesis an analysis of TLPA’s with the support of logistics as a way to foster local endogenous development, having as case study the City of Guaramiranga. The results has showed synthetically a low participation and interrelation of the local actors, beyond a negative evaluation of the services offered for the studied establishments.